Non‐pharmacological treatments for COPD. Issue 5 (21st April 2016) - Mulhall, Patrick; Criner, Gerard
Abstract: Chronic obstructive pulmonary disease (COPD) affects roughly 10% of the global population and is growing in prevalence annually. COPD is characterized by progressive non‐reversible narrowing of airways mainly due to cigarette smoking. Therapeutic interventions aimed at altering this progressive disease course can largely be grouped into pharmacological or non‐pharmacological therapies. The focus of this paper is on the non‐pharmacological aspects of COPD management, reviewing the current literature to provide an evidence‐based management approach. Non‐pharmacological therapies reviewed in this article include the implementation of comprehensive care models utilizing a coordinated multidisciplinary team, tele‐monitoring and patient‐centred approach to optimize COPD care and improve compliance. Preventing progression of COPD via smoking cessation remains of paramount importance, and newer therapeutic options including electronic cigarettes show promise in small studies as cessation aids. COPD has systemic manifestations that can be ameliorated with the enrollment in pulmonary rehabilitation programmes, which focus on exercise endurance to improve dyspnoea and quality of life. Advanced therapeutics for COPD includes lung volume reduction surgery for a pre‐specified cohort and minimally invasive bronchoscopic valves that in recent reviews show promise. Lastly, patients on maximal COPD therapy with progressive disease can be referred for lung transplantation; however, this often requires a highly selected and motivated patient and care team. Survival rates for lung transplantation are improving; thus, this procedure remains a viable option as more expertise and experience are gained.